2011
DOI: 10.15835/nbha3926379
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Use of Carbon Isotope Discrimination as a Selection Tool of Perennial Fodder Species for Temporary Pastures

Abstract: Estimation of the relationship between carbon isotope discrimination (Δ13C) in perennial fodder plants and various factors such as climate, fertilization and soil could contribute to a better selection and/or improvement of genotype of fodder species. Theoretical models of carbon isotope discrimination in plants indicate a linear relationship between Δ13C and CO2 partial pressures ratio (pi/pa) from the intercellular spaces (pi) of CO2 in leaves and from the atmosphere (pa). It is also known that between pi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…They showed the increased growth of Napier grass in intercropping with legumes as compared to sole napier grass. Sima et al (2010) concluded that, the utilization of symbiotically fixed nitrogen, improved light absorption and other benefits made the triple rows of cowpea preferable to the double or single row. Similar findings were made by Lakshmi and Anita (2020).…”
Section: The Effect Of Cowpea Intercropping and Different Fertilizer ...mentioning
confidence: 99%
“…They showed the increased growth of Napier grass in intercropping with legumes as compared to sole napier grass. Sima et al (2010) concluded that, the utilization of symbiotically fixed nitrogen, improved light absorption and other benefits made the triple rows of cowpea preferable to the double or single row. Similar findings were made by Lakshmi and Anita (2020).…”
Section: The Effect Of Cowpea Intercropping and Different Fertilizer ...mentioning
confidence: 99%